PREVALENCE AND PATHOLOGY OF DICTYOCAULUS VIVIPAROUS INFECTION IN CATTLE AND BUFFALOES - F. Mahmood; A. Khan; R. Hussain; M. S. Anjum (Journal of Animal and Plant Sciences, 2014)
The nematode, Dictyocaulus viviparus, causes severe parasitic bronchitis in dairy animals and is responsible for significant economic losses. Present study was conducted to determine the occurrence of bovine lungworm Dictyocaulus viviparus ahighly endemic parasite. The fecal samples were collected from buffaloes (n=235) and cattle (n=210) and examined using Baermann technique. After slaughtering the lungs of all the buffaloes and cattle were separated and carefully examined for the presence of D. viviparus at Faisalabad abattoir.Overall non-significant difference in prevalence of D. viviparus in fecal samples of cattle (4.76%) and buffaloes (5.10%) was recorded. Grossly morbid lung tissues from buffalo (n=5) and cattle (n=3) revealed nodular appearance, severe pneumonia and congestive changes. Multifocal lymphocytic and eosinophilic bronchiolitis along with widened interlobular pulmonary septa were observed in lungs sections infected with D. viviparus. Lungs tissue exhibited peribronchiolar aggregation of mononuclear cells, presence of eggs and different developmental stages including, newly hatched and L1 stage of D. viviparus in air spaces.
Keywords: Buffaloes; Cattle; Nematode; Dictyocaulus viviparus; Lungs; Pathology.